Estudo da interação entre as vitaminas lipossolúveis com cádmio e chumbo por ASV em meio orgânico - Sauer, Michele Pokulat (2006)
In this work two voltammetric methods were investigated to study the interaction between metals, Cd and Pb, and fat-soluble vitamins (retinol palmitate VA; cholecalciferol VD; α-tocopherol acetate VE; filloquinona - VK). Due to hydrophobic characteristic of these vitamins, the voltammetric measurements were conducted in non aqueous media. In the first method (Method I) acetone was used was used as organic media, tetrabutylamonium iodide (ITBA) 0.2 mol L-1 as electrolyte and an electrode modified reference with double liquid junction - Ag/AgCl/LiCl saturated in ethanol/ITBA 0.02 mol L-1 in N,N - dimetylformamide (DMF). In the second method (Method II) ethanol was used as organic media, acetate buffer pH the 4.6 (in ethanol) as electrolyte and an electrode modified reference with double liquid junction - Ag/AgCl/LiCl saturated in ethanol/acetate buffer pH 4,6 (in ethanol). During the method development the behavior of Cd and Pb in studied conditions was evaluated. Each vitamin was studied individually. Method I was not the more adequate to study the interaction metal-vitamin because in most of the case the vitamin additions caused an increase on the voltammetric signals. Method II presented reduction of the Cd and Pb signals and the anodic shift of peak potentials in presence of the vitamins. The reduction of the signals increased in the order: VK < VD < VE < VA. High peak reduction was observed for Pb with the VA, VE and VD and for Cd with the VK. Measurements of alternating current voltammetry were also investigated to study the adsorption of vitamins on the electrode surface. Comparing the results obtained by the anodic stripping voltammetry with the results by alternated current, it was observed that the variations on the voltammetric signals are related predominantly with to adsorptions of VA and VD while to VE and VK the effect of adsorption was not predominant.